Digital Marketing Strategy and Product Innovation Hampers: A Case Study of Askara Kayu Karanganyar Paiton Probolinggo - Himmah, Mufidatul; Hotimah, Husnul; Maulida, Bela Nur (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the digital marketing strategy and product innovation implemented by the MSME Askara Kayu, located in Karanganyar, Paiton, Probolinggo. Established in 2019, Askara Kayu focuses on producing wood-based hampers, which have become a trend in the creative economy industry, particularly in the MSME sector. This research employs a qualitative approach with a case study method. Data collection techniques include in-depth interviews with the business owner and direct observation of the production and marketing processes. The research findings show that Askara Kayu's success is supported by several key factors, namely consistency in maintaining product quality, design innovation that aligns with market trends, and attractive product visualization across various digital platforms. The digital marketing strategies applied include the use of social media such as Instagram and marketplaces like Shopee and Tokopedia. Additionally, Askara Kayu optimizes paid advertisements such as Meta Ads to expand market reach. The target market segments include individual consumers, corporate institutions, and public figures. Family involvement and a network of local artisans also contribute to increasing production capacity and ensuring business sustainability. The findings of this study are expected to serve as a reference for other MSMEs in developing digital marketing strategies and product innovations based on creativity.